Reformulation of standardised neonatal parenteral nutrition to improve nutrient delivery. Issue 6 (9th May 2013) - Bevan, A; Johnson, M; Pond, J; Lansdowne, Z; Leaf, A; Hayes, P; Pearson, F
Abstract : Postnatal growth failure is common in preterm infants and one reason for this is that nutritional care is often variable and suboptimal. Achieving targets for nutrient intakes in this group of patients is difficult, particularly in the first few weeks of life when they are reliant on parenteral nutrition (PN). Aims: We aimed to improve nutrient delivery to preterm infants on the Neonatal Intensive Care Unit by the provision of an improved, all inclusive standardised PN supply from ready made bags and lipid syringes. In addition, we aimed to reduce the need for bespoke PN bags made in pharmacy in line with the local manufacturing unit capacity plan. Methods: Existing ready made PN bags were compared with recommendations from the European Society of Paediatric Gastroenterology, Hepatology and Nutrition, and felt to be inadequate. New, more concentrated formulations were proposed and checked to allow a minimum stability of 28 days. Three bags were re-formulated, a 'preterm' bag (sodium free, 28 day stability), a 'preterm plus sodium' bag and a 'term' bag (both 3 months stability).The new formulations were agreed with the neonatal clinical and nutrition teams. Data on daily nutrient delivery during the first 2 weeks of life were collected prospectively following the introduction of the improved solutions, from 1 August to 31 December 2011 (Period 2). This was compared with data from a retrospective cohort of preterm infants born during 2009 (Period 1). Results: 64 infants born during Period 1 (mean gestational age and weight at birth 28.6 weeks and 1.07 kg respectively) were compared with 36 born during Period 2 (mean gestational age and weight at birth 29.2 weeks and 1.03 kg respectively). Median values for nutrient intake were calculated, and the two periods compared using the Mann-Whitney U test. During the first week of life, energy delivery improved from 63.6 to 70.0 kcal/kg/day, protein delivery from 1.8 to 2.0 g/kg/day, carbohydrate delivery from 10.2 to 11.5 g/kg/day, fat delivery from 1.3 to 1.6/kg/day, vitaminCQ1: Please check the text 'fat delivery from 1.3 to 1.6/kg/day'. A delivery from 218.3 to 330.0 IU/kg/day, vitamin D delivery from 35.3 to 54.7 IU/kg/day and vitamin E delivery from 0.7 to 1.1 IU/kg/day (p<0.01 for all except carbohydrate). In the second week of life, energy delivery improved from 113.8 to 121.4 kcal/kg/day and protein delivery from 2.7 to 3.1 g/kg/day (p<0.01 for both). Delivery of carbohydrate, fat and vitamins A, D and E did not change significantly. Conclusions: Reformulating ready made PN solutions significantly increased macro- and micronutrient delivery during the first week of life, and protein delivery during week two. Providing optimal nutrition to preterm infants is complicated by their need for other infusions, such as inotropes, reducing the volume available for PN. Concentrated formulae allow more nutrition to be delivered, more closely mimicking placental nutrient delivery. Providing an appropriately formulated complete standardised PN solution with appropriate levels of electrolytes can improve the nutritional intake of preterm infants.